Attitudes towards machismo and emotional regulation in university students of Metropolitan Lima - Huerta Rosales, Rosa Elena (2021)
The study analyzed the relationship between attitudes towards machismo and emotional regulation, according to public and private university and sex; In a sample of 830 students, 405 men (48.8%) and 425 women (51.2%), aged between 18 and 32 years, who were examined with a data sheet, the Scale of Evaluation of Attitudes towards machismo and the Emotional Regulation Questionnaire. A positive and statistically significant relationship is found between the cognitive reappraisal strategy with the rejection of total machismo and an inverse relationship with suppression and the six areas of machismo. Likewise, there is an association, in women, between the rejection of machismo with cognitive and inverse and significant reevaluation with the suppression in both sexes. Those from public universities obtain a statistically significant and positive correlation between cognitive reappraisal and rejection of global machismo. Those from private universities show greater rejection of machismo. The restructuring of meaning lessens the effects of stress. Although suppression modifies the expression of the emotional response but does not alter the nature of the negative emotion, leaving latent the propensity for machismo and gender violence common to all social classes and cultures.